Pengaruh Ekuitas Merek Terhadap Minat Beli (Studi Pada Konsumen Oronamin C di Kota Bandung) - Qonita Firdaus; Tintin Suhaeni (Jurnal Riset Bisnis dan Investasi, 2020)
Amid the growth of functional beverage industry, Oronamin C is still new on the market so the strength of this brand is still not very visible. Therefore, this study purpose is to determine the effect of Oronamin C’s brand equity on consumer purchase intention. This study uses an explanatory descriptive method with a quantitative approach to 150 respondents. The data analysis method used is descriptive statistics analysis, correlation, multiple regression, hypothesis testing. The results showed that brand equity and purchase intention were in the good category and both had a significant effect of 65.5%. The dimensions of brand equity, brand awareness and brand loyalty, are in the moderate category, while brand association and perceived quality are in the good category. With the significant influence between perceived quality and brand loyalty on purchase intention, and there is an insignificant influence between brand awareness and brand association on purchase intention.